Trinidad Hilton Hotel - (:unkn) unknown (Y. De Lima and Co. Ltd., Trinidad, 2010)
The postcard shows the pool and pool terrace of the Trinidad Hilton.
Coloured: Colour; Style: Landscape; Other: Unbordered, Divided
Keywords: Trinidad and Tobago; Postcards; Hotels; Port of Spain